2018
DOI: 10.1038/s41419-018-0508-y
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitor of apoptosis proteins are required for effective fusion of autophagosomes with lysosomes

Abstract: Inhibitor of Apoptosis Proteins act as E3 ubiquitin ligases to regulate NF-κB signalling from multiple pattern recognition receptors including NOD2, as well as TNF Receptor Superfamily members. Loss of XIAP in humans causes X-linked Lymphoproliferative disease type 2 (XLP-2) and is often associated with Crohn’s disease. Crohn’s disease is also caused by mutations in the gene encoding NOD2 but the mechanisms behind Crohn’s disease development in XIAP and NOD2 deficient-patients are still unknown. Numerous other… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 42 publications
(36 reference statements)
1
21
0
Order By: Relevance
“…The defect in bacterial clearance given by the NPC1 variant can be overcome by pharmacological activation of autophagy [77]. Recently, it was revealed that inhibitors of apoptosis proteins, such as XIAP, are required for the fusion of autophagosome with lysosome during autophagy [78]. Inhibition or loss of function of inhibitor of apoptosis proteins results in impaired autophagic flux, responsible for defective mitophagy and impaired bacterial clearance, and increased secretion of TNF and IL1B, which may lead to CD development [78].…”
Section: Autophagy and Innate And Adaptive Immune Responsesmentioning
confidence: 99%
See 1 more Smart Citation
“…The defect in bacterial clearance given by the NPC1 variant can be overcome by pharmacological activation of autophagy [77]. Recently, it was revealed that inhibitors of apoptosis proteins, such as XIAP, are required for the fusion of autophagosome with lysosome during autophagy [78]. Inhibition or loss of function of inhibitor of apoptosis proteins results in impaired autophagic flux, responsible for defective mitophagy and impaired bacterial clearance, and increased secretion of TNF and IL1B, which may lead to CD development [78].…”
Section: Autophagy and Innate And Adaptive Immune Responsesmentioning
confidence: 99%
“…Recently, it was revealed that inhibitors of apoptosis proteins, such as XIAP, are required for the fusion of autophagosome with lysosome during autophagy [78]. Inhibition or loss of function of inhibitor of apoptosis proteins results in impaired autophagic flux, responsible for defective mitophagy and impaired bacterial clearance, and increased secretion of TNF and IL1B, which may lead to CD development [78]. In addition to an efficient fusion of autophagosome with lysosome, a functional lysosome is also required to guarantee pathogen elimination.…”
Section: Autophagy and Innate And Adaptive Immune Responsesmentioning
confidence: 99%
“…This was reported to be associated with decreased xenophagy in a manner similar to loss of function of two other well-known Crohn’s Disease associated proteins, Nod2 and XIAP (Schwerd et al, 2017), both of which also positively regulate autophagy (Homer et al, 2010; Gradzka et al, 2018). Mutations in NOD2 lead to loss of NF-κB activation, as do many of the mutations in XIAP that are associated with disease, suggesting that failure to activate this pathway is the initial cause of the pathology, however, recent studies have shown that NOD2 and XIAP both also have roles in targeting invasive bacteria for xenophagy (Homer et al, 2010; Gradzka et al, 2018). How this may be coordinated is not clear, but the association of other autophagy related mutations such as the Atg16L1, NDP52, Optineurin, and others CD suggest that specific defects in the autophagy process may be a key trigger as well.…”
Section: Autophagy Receptors Acting As Signaling Scaffolds Toomentioning
confidence: 92%
“…Even though targeting IAPs including XIAP, cIAP1, and cIAP2 by a Smac mimetic, APG-1387, was shown to induce autophagy and cell death in human ovarian cancer cells [47]; contrary, addition of a different Smac mimetic, LCL161 (a drug known to target cIAP1, cIAP2, and XIAP), at high dose was shown to inhibit the fusion between autophagosome and lysosome in mouse embryonic cells (MEFs) [48]. Downregulations of cIAP2 and XIAP by siRNA were demonstrated to induce similar cellular phenotypes in MEFs [48], further suggesting that XIAP can act as an autophagy suppressor, despite the detailed molecular mechanism remains to be determined. Noticeably, XIAP and cIAP1 have also been suggested to positively-regulate the expression of Beclin 1, which is a protein crucial for the biogenesis of autophagosome during canonical autophagy, via an nuclear factor-κB (NFκB)-signaling pathway [49].…”
Section: Xiap As a Controversial Autophagy Modulatormentioning
confidence: 99%